2017
DOI: 10.1038/sj.bdj.2017.405
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cervical resorption and the oro-facial cleft patient: a review and case series

Abstract: Introduction Invasive cervical resorption (ICR) has an unknown aetiology, yet it exhibits very aggressive behaviour compared with typical external root resorption, posing a high risk of tooth loss.Aim To investigate the number of patients at the Dublin Cleft Prosthodontic Department with an oro-facial cleft who experienced ICR and to identify any possible aetiological factors.Materials and method A retrospective investigation of all oro-facial cleft patients treated at the Dublin Cleft Prosthodontic Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…In a case of carefully investigated multiple IRRs, the pulp wall visible within the lesion on the native specimen in two-dimensional radiograph could not be visualized on μCT (49). Localization of CRR obviously is multifactorial: CRR was recorded in cleft palate patients only in the maxilla (43).…”
Section: Cgcl In Nsmentioning
confidence: 97%
See 1 more Smart Citation
“…In a case of carefully investigated multiple IRRs, the pulp wall visible within the lesion on the native specimen in two-dimensional radiograph could not be visualized on μCT (49). Localization of CRR obviously is multifactorial: CRR was recorded in cleft palate patients only in the maxilla (43).…”
Section: Cgcl In Nsmentioning
confidence: 97%
“…However, (invasive) cervical root resorption (CRR) of teeth differs from apical root resorption by lesion's localization (apical vs. cervical), extension (limited shortening of the apex vs. dissolution of the middle third of the root) and consequences to tooth preservation (normally shortened, vital tooth vs. extensive destruction of the hard tissues and tooth loss) (39)(40)(41)(42)(43)(44)(45)(46)(47). CRR has also been reported several times in orthodontics, is a rare phenomenon and usually affects a single tooth.…”
Section: Cgcl In Nsmentioning
confidence: 99%
“…Heithersay em 1999 estimou uma prevalência de 0,02% de RCE na cidade de Adelaide (Austrália) considerando uma amostra de 222 pacientes de um total de 1,2 milhão de habitantes da cidade na época, com maior predileção pelo sexo feminino (114 pacientes), idade média de 37 anos, acometendo preferencialmente o incisivo central superior (n=75) (HEITHERSAY, 1999a). Um estudo realizado em Dublin (Irlanda), investigou 588 pacientes com fissura lábio-palatina, os quais exibiram uma baixa prevalência (2,38%) de RCE na população alvo, maior predileção pelo sexo feminino (53%), com idade média de 28 anos, maior predileção por incisivos centrais superiores (65%) e histórico de tratamento ortodôntico em todos os pacientes investigados (O'MAHONY et al, 2017). Já um estudo realizado com 276 pacientes em Guangzhou (China), descreveu a ocorrência de vários tipos de reabsorções radiculares externas relacionadas com a presença de terceiros molares impactados (LI et al, 2019).…”
Section: Conhecendo a Reabsorção Cervical Externaunclassified
“…There are several predisposing factors reported in relation to the loss of the protective layers and ICR. Among these factors, trauma, orthodontic treatment, and periodontal treatment that could cause physical damage to precementum showed strong correlations with ICR [ 18 , 19 , 20 , 21 , 22 , 23 ]. Heithersay, in the analysis of predisposing factors from 222 patients with 257 ICR teeth, reported that orthodontic treatment (24.1%) was the most common factor, and trauma (15.1%) was the second most common [ 1 ].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…There is limited information regarding the outcomes of treatment for ICR lesions due to the scarcity of clinical outcome studies. A majority of studies are case reports and case series [ 8 , 20 , 21 , 52 , 53 , 55 , 62 , 63 , 64 , 65 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], and it may be difficult to predict the prognosis of treated teeth based on those studies because only successful cases tend to be reported. Furthermore, due to the disease rarity, clinical studies may seem difficult to perform.…”
Section: Prognosismentioning
confidence: 99%